Idiopathic Hypokalemia in Lupus Nephritis: A Newly Recognized Entity. Issue 10 (28th October 2021) - Adomako, Emmanuel A.; Bilal, Saira; Liu, Yu-lun; Malik, Ayesha; Van Buren, Peter N.; Shastri, Shani; Sambandam, Kamalanathan K.
Visual Abstract: Abstract : Key Points: Hypokalemia may occur in patients with lupus nephritis in the absence of renal tubular acidosis (RTA) or other known causes. Patients with lupus nephritis and idiopathic hypokalemia have a distinct pattern of markers of autoimmunity. Clinically evident RTA in lupus nephritis exhibits a distinct pattern of markers of autoimmunity. Background: Various causes of hypokalemia (HK) from renal potassium wasting, including distal renal tubular acidosis (RTA), have been described in lupus nephritis (LN). We report a phenomenon of otherwise unexplained HK among a population with LN. Methods: From our population of 403 patients with LN, we identified a cohort of 20 patients with idiopathic HK, defined by serum potassium <3.5 mmol/L without any apparent explanation. This cohort is compared with 90 LN controls (CON) and ten patients with LN with distal RTA from the same population. Results: The patients with HK had lower median serum potassium compared with CON and RTA subjects (3.26 versus 4.00 versus 3.75 mmol/L, respectively; P <0.001). The median serum bicarbonate was normal in HK and CON, but low in RTA (26.0 versus 25.0 versus 19.4 mmol/L; P <0.001). The median urine pH was abnormally high only in the RTA group (6.00 versus 6.25 versus 6.67; P =0.012). The median serum magnesium was modestly lower in HK compared with the CON and RTA groups (1.73 versus 2.00 versus 1.85 mg/dl; P =0.002). Although both HK and RTA showed a higher rate of seropositivity than CON for anti-Ro/SSA (79% and 80% versus 37%, respectively; P <0.001), only HK revealed a higher rate of seropositivity than CON for anti-RNP (84% versus 42%; P =0.003) and only RTA showed a higher rate of seropositivity than CON for anti-La/SSB (40% versus 12%; P =0.05). Conclusions: A syndrome of idiopathic HK was revealed in 20 out of 403 (5%) of patients within our LN population, and proved to be distinct from the RTA that occurs in LN. Furthermore, it was associated with a distinct pattern of autoantibodies. We speculate that idiopathic HK is the result of a novel target of autoimmunity in LN, affecting renal tubular potassium transport.